Ergosterol and polyphenol contents as rapid indicators of orchardgrass silage safety - Alba-Mejía, Jhonny E; Dohnal, Vlastimil; Domínguez-Rodríguez, Gloria; Středa, Tomáš; Klíma, Miroslav; Mlejnková, Veronika; Skládanka, Jiří (Heliyon, 2023)
The ergosterol (ERG) has been proposed as a potential indicator of fungal contamination, along with polyphenol content analysis to predict silage safety. Despite efforts in controlling fungal growth in silage, mycotoxin co-contamination represents a possible risk for animal and human health. Modern analytical techniques determine a multitude of fungal metabolites contaminating feed. Nonetheless, these methods require sometimes arduous sample pre-treatment, long separation times, and expensive standard compounds to identified contaminants. Thus, the goal of this study was to suggest a rapid analysis of ERG and polyphenol contents to assess silage hygienic quality in ten orchardgrass varieties ensiled without and with biological and chemical additives. The determination of ERG on samples was performed by high-performance liquid chromatography using UV detection and UV/Vis spectrophotometry to determine the polyphenol content. Statistically significant differences (P < 0.05) between varieties, years and silage additives were found. Bepro was the unique variety that did not present ERG in the first cut in 2012. ERG content increased in the first cut in 2013 using biological additives as well as ERG and polyphenol contents in the first cut in 2013 using chemical additives compared with untreated silage. In addition, biological and chemical additives used in this study did not satisfactorily reduce the content of ERG and polyphenols in silage grass. Consequently, our results provide fast information about the progressive fungal contamination of grass silage. To our knowledge, it is the first time that the presence of ERG and polyphenols is determined in ten different orchardgrass varieties treated without and with additives. In general, ERG and polyphenol contents showed to be good indicators of orchardgrass silage safety.
Keywords: Silage quality; Dactylis glomerata; Livestock; Additives; Fungal marker